1963
DOI: 10.1111/j.1399-6576.1963.tb05480.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory Effects of Succinylcholine in Man

Abstract: SUMMARY The effects of intravenous (standard apnoeic) and intra‐arterial doses of succinylcholinc chloride (SCh) on peripheral circulation (forearm, hand, skeletal musculature, skin, mucosa of the sigmoid colon), arterial blood pressure and heart rate were studied in 15 unanaesthetized and 17 anaesthetized subjects. Standard apnoeic doses of SCh injected intravenously in anaesthetized subjects produced circulatory changes usually of a biphasic character, a sudden initial decrease in peripheral blood flow and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

1966
1966
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 198 publications
(238 reference statements)
0
5
1
Order By: Relevance
“…From the present experiments it was concluded that stimulation of autonomic ganglia and respiratory depression both contributed towards the overall changes in cardiovascular function in horses anaesthetized with halothane. The differing findings of the present and previous authors may be due to the use of different general anaesthetic agents (Graf et al, 1963). That the general anaesthetic may modify the cardiovascular effects of suxamethonium is apparent from the present results in horses anaesthetized with ether, in which only minor cardiovascular changes were recorded.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…From the present experiments it was concluded that stimulation of autonomic ganglia and respiratory depression both contributed towards the overall changes in cardiovascular function in horses anaesthetized with halothane. The differing findings of the present and previous authors may be due to the use of different general anaesthetic agents (Graf et al, 1963). That the general anaesthetic may modify the cardiovascular effects of suxamethonium is apparent from the present results in horses anaesthetized with ether, in which only minor cardiovascular changes were recorded.…”
Section: Discussioncontrasting
confidence: 83%
“…This development of tolerance is in contrast to the findings of Hansson (1958), who did not observe tachyphylaxis to suxamethonium in horses under pentobarlbitone anaesthesia, and to the findings of Thesleff (1952) and Conway (1961) in the cat. Tachyphylaxis to the neuromuscular blocking and cardiovascular effects of suxamethonium has been recorded, however, iby other workers in isolated muscle preparations (Freeman, 1967), and in the intact dog (Stevenson, 1960a), cat (Adams & Hall, 1962), and man (Graf et al, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…When the smaller dose of anticholinergic was used, it was noted that a modest slowing of the heart rate following, say, the third dose of suxamethonium, would often lead to a more severe decrease after subsequent doses. There was no evidence of tachyphylaxis to repeated doses as has been reported in some studies (Graf, Strom and Wahlin, 1963). One might ask why a non-depolarizing agent was not used.…”
Section: Discussionmentioning
confidence: 65%
“…Succinylcholine chloride is thought to have transient and minor effects on the circulatory system. However, it was found to be a general vasodilator, with vasodilation caused in part by its local action on the peripheral circulation 66 . This effect could have influenced our findings, particularly those obtained during induced respiratory acidosis with succinylcholine chloride administration.…”
Section: Discussionmentioning
confidence: 72%
“…However, it was found to be a general vasodilator, with vasodilation caused in part by its local action on the peripheral circulation. 66 This effect could have influ- The present study provided an ideal environment for collecting "arterialized" venous blood. Nevertheless, the PCO 2 of the ASV had a systematic bias of +3 mm Hg when compared with the arterial value.…”
Section: Discussionmentioning
confidence: 96%